The Exchange That Changed My Life (Comparative & International Education Series, 2022)
My name is Nerea Pedreira, and I am a 20-year-old Tourism undergraduate enrolled at the University of Vigo, Spain. I would like to share my story of summer 2018. I had just been awarded a scholarship that enabled me to take part in an International Summer School, which took place in the city of Bremerhaven, located in northern Germany.